2022
DOI: 10.1088/1361-665x/ac980e
|View full text |Cite
|
Sign up to set email alerts
|

3D printed multi-material polylactic acid (PLA) origami-inspired structures for quasi-static and impact applications

Abstract: Origami patterns can be used to inspire the designs of structural materials with beneficial properties, such as low strength-to-weight ratios. This study explores the design, manufacturing, and mechanical properties of three different origami-inspired shapes, as well as three different material combinations for each shape, through dynamic impact testing and quasi-static compression testing. The commonly studied Miura origami pattern will be compared to two uncommon patterns: a square-based pattern and a triang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This includes fabrication techniques like the utilization of the natural buckling patterns [14,15] or 3D and 4D printing. [16][17][18] Additional applications focus on deployable structures, [19,20] innovative robotic arms [21,22] which are actuated by magnetic fields [23] or pressure, [24][25][26] and agile crawling robots, [27][28][29] which are also actuated by magnetic fields [30,31] or pressure. [32,33] The potential of the pattern extends even to the fields of energy absorption [34,35] and harvesting, [36,37] and it has been found that geometrical configuration can enhance the design and performance of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…This includes fabrication techniques like the utilization of the natural buckling patterns [14,15] or 3D and 4D printing. [16][17][18] Additional applications focus on deployable structures, [19,20] innovative robotic arms [21,22] which are actuated by magnetic fields [23] or pressure, [24][25][26] and agile crawling robots, [27][28][29] which are also actuated by magnetic fields [30,31] or pressure. [32,33] The potential of the pattern extends even to the fields of energy absorption [34,35] and harvesting, [36,37] and it has been found that geometrical configuration can enhance the design and performance of the structure.…”
Section: Introductionmentioning
confidence: 99%
“…There are two available alternatives for altering the crease characteristic, i.e., changing the material at the crease and modifying the geometrical configuration of the crease. Changing the material properties at the crease may lead to difficulty in manufacturing due to the multi-material fabrication [40]. Thus, altering the geometrical configuration at the crease is a preferable option.…”
Section: Introductionmentioning
confidence: 99%
“…Changing the material properties at the crease may lead to manufacturing difficulties owing to multimaterial fabrication. [ 41 ] Therefore, altering the geometric configuration of the crease is preferable. Size optimization makes a limited contribution to improving the performance of origami structures.…”
Section: Introductionmentioning
confidence: 99%